Measuring Neurobehavioral Disabilities Among Severe Brain Injury Survivors: Reports of Survivors and Proxies in the Chronic Phase - Soendergaard, Pernille Langer; Siert, Lars; Poulsen, Ingrid; Wood, Rodger Ll.; Norup, Anne (Frontiers in Neurology, 2019)
Background: Neurobehavioral disability (NBD) has a major influence on the long-term psychosocial outcome following acquired brain injury, as it affects not only the survivor of the brain injury, but the whole family. Objectives: To investigate 1) the frequency of NBD among survivors of severe brain injury measured by the Danish version of the St Andrew’s-Swansea Neurobehavioural Outcome Scale (SASNOS) rated by patients and proxies, 2) factors associated with NBD, and 3) concordance between reports of NBD completed by patients and proxies. Methods: SASNOS was administered at an outpatient unit as a part of a follow-up assessment after discharge from intensive neurorehabilitation. SASNOS consists of five factors describing the following domains: Interpersonal Behaviour, Cognition, Aggression, Inhibition and Communication, and both the patient and a proxy were asked to complete the questionnaire. Data collection was conducted over a period of two years. 32 patients and 31 proxies completed the questionnaire. Mean time since injury was 19.4 months (10.0 SD). Most patients were male (68.8%), and most proxies were female (58.1%). Most of the patients had suffered a traumatic brain injury (68.8%) Results: A fourth of this patient group reported themselves as below the normal range on the major domains of Interpersonal Behaviour and Cognition. Significant associations between proxies’ reports and time since injury, cohabitant status, and the patient’s score on the Extended Glasgow Outcome Scale were found. Furthermore, significant differences were found between patient and proxy ratings. Proxies rated patients as having fewer problems on the Interpersonal Behaviour domain, and more problems in relation to Cognition. Cognition was the only domain, where patients rated themselves higher indicating fewer problems, compared with their proxies. On both the Aggression and Communication domains, proxies rated patients higher indicating fewer problems than the patients themselves. Conclusion: Danish brain injury survivors experienced NBD as measured by SASNOS. Differences were found between patient and proxy ratings in relation to Cognition and Interpersonal Behaviour. The NBDs identified can affect the survivor’s ability to reintegrate and participate in activities of daily living, emphasizing how a systematic assessment, followed by a tailored interview, might help the survivors and their family.